EVOLUTION OF THE LUNAR CRUST: SIMS STUDY OF PLAGIOCLASE FROM FERROAN ANORTHOSITES - Papike J.J.; Fowler G.W.; Shearer C.K. (My University, 1997)
The lunar crust, down to a depth of ~65 km, is composed of older (>4.5 Ga) ferroan anorthosites and younger (4.43-4.17 Ga) Mg-suite lithologies which include dunites, troctolites, and norites. The anorthosites are generally inferred to represent floating cumulates in a lunar magma ocean (possible depth 800 km, moon's radius ~1,738 km). The cumulates that are inferred to be located near the base of the magma ocean are dominantly olivine and pyroxene. The last dregs of the magma ocean are enriched in incompatible elements and have been named KREEP (K, rare earth elements, P). KREEP, formed in this manner, is probably concentrated near the crust/mantle boundary at ~70 km depth. We are attempting to characterize melts parental to ferroan anorthosites and Mg-suite norites by analyzing REEs (La, Ce, Nd, Sm, Eu, Dy, Er, Yb) and Ba, Sr, and Y in their cumulus plagioclase. If the cumulus grains have not been compromised by postcrystallization effects and if we know the relevant mineral/melt partition coefficients (Ds) we can invert the trace element data for plagioclase to parental melt compositions. Melts parental to ferroan anorthosites are estimated to contain REE at concentrations ten to fifty times chondrites. Melts parental to the earlier crystallizing anorthosites (lower REE) have virtually no Eu anomaly, while melts parental to later crystallizing anorthosites (higher REE) have small negative Eu anomalies. This is qualitatively consistent with the fractionation of Eu relative to other REE by crystallization of plagioclase with large positive Eu anomalies. Melts parental to the Mg-suite have much higher total REE and very large negative Eu anomalies. The characteristics of Mg-suite norite parental magmas may have been derived by the assimilation of KREEP (near the crust/mantle boundary) by Mg-rich basaltic melts formed deeper in the cumulate pile or near the contact between the lower cumulate horizons of the magma ocean and primitive, unprocessed lunar mantle (~800 km).